Dinamika Elit Gereja dalam Panggung Politik - Deki Itje; Laila Kholid Alfirdaus (Mahesa Research Center, 2021)
The church is an organizational organization that takes the interests of various church elites and parties to become a competition arena for local political elites. Thus, the elite church became the target of political elites and academics who wanted to seize power. This condition is evident, in various political constellations, religious organizations are laden with political contracts. Involve church elites in political momentum, there is support and response. This research explains how church elites compete on the political front and the views of church members of the church involved in politics. The methodology used is descriptive qualitative by determining informants using a purposive technique, in which the informants are determined based on their capacity to answer questions that are the locus of this study. The informants in the study were 13 people. The research location is in North Halmahera Regency. The results of the research show that political momentum contains political views and interests, thus giving permission to the church split (GMIH). The church elite (pastor) with its theological mission transformed into a practical political mission, the community (congregation) was educated with the political education of race, ethnicity, and religion which was then considered as the truth that all levels of society must accept.